2020
DOI: 10.1111/hsc.12918
|View full text |Cite
|
Sign up to set email alerts
|

Instability in daily life and depression: The impact of sleep variance between weekday and weekend in South Korean workers

Abstract: South Korean workers have problems getting optimal sleep because they work excessively, and this affects their sleep duration and quality. To compensate for their lack of sleep on weekdays, South Korean workers have a different lifestyle on weekends, which is reflected by the terms ‘Hot Friday’ and ‘Monday Sickness’. However, an irregular lifestyle may be a risk factor for poor health even if insufficient sleep during weekdays is supplemented by sleep on the weekend. The objective of this study was to analyse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
7
1
Order By: Relevance
“…This result concurred with previous ndings that indicated that both short and long sleep durations increased the risk of depression among adults who participated in seven prospective studies [24]. Short sleep durations seem to negatively affect one's depressive state by increasing daytime tiredness [27], which predicts the risk of depression [25]. Daytime tiredness, which includes sleepiness and fatigue, increases negative events and negative emotional states that predispose individuals to depression [26].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result concurred with previous ndings that indicated that both short and long sleep durations increased the risk of depression among adults who participated in seven prospective studies [24]. Short sleep durations seem to negatively affect one's depressive state by increasing daytime tiredness [27], which predicts the risk of depression [25]. Daytime tiredness, which includes sleepiness and fatigue, increases negative events and negative emotional states that predispose individuals to depression [26].…”
Section: Discussionsupporting
confidence: 91%
“…This indicates that both excessive sleeping time and irregular weekend-centered sleeping patterns increase the risk of depression. Although the variation of sleep duration on weekdays and weekends was associated with depressive symptoms in South Korean workers, the direction of this association has not been clari ed before [27]. In contrast, we found that sleeping more on weekends was associated with a lower risk of depression in women who slept less than 5.9 hours per day on average.…”
Section: Discussioncontrasting
confidence: 83%
“…In fact, studies show that the number of surgeries performed for lung cancer has increased in large cities where tertiary hospitals are located [25]. In particular, 60% of lung cancer surgeries were conducted in tertiary hospitals located in the capital area and most patients were receiving radiation therapy in Seoul [25,27]. In terms of healthcare resources, well-equipped medical equipment and physician volume can lead to better patient outcomes [28], which in turn can affect mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found that Service members and veterans who had higher PTSD, depression and anxiety scores were those who had relatively bad or very bad sleep quality (39). A study among South Korean workers found that the variance in weekday and weekend sleep duration are highly associated with PHQ-9 score which indicated depression (40). A recent research suggested that poor sleep quality and social support lead to anxiety, stress and self-e cacy problems among HCWs in China dealing with COVID-19 during early stages of the outbreak (41), which is consistent with our study.…”
Section: Risk Factors Associated With Psqi Depression Anxiety and Ptsdmentioning
confidence: 98%